The relation of patient dependence to home health aide use in Alzheimer's disease. - Scherer, Rachel K; Scarmeas, Nikolaos; Brandt, Jason; Blacker, Deborah; Albert, Marilyn S; Stern, Yaakov (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: Although there has been much research devoted to understanding the predictors of nursing home placement (NHP) in Alzheimer's disease (AD) patients, there is currently a lack of research concerning the predictors of home health care. The objective of this study was to examine whether the Dependence Scale can predict home health aide (HHA) use. METHODS: The sample is drawn from the Predictors Study, a large, multicenter cohort of patients with probable AD, prospectively followed annually for up to 7 years in three university-based AD centers in the United States. Markov analyses (n=75) were used to calculate annual transition probabilities for the "new onset" of HHA use (instances where an HHA was absent at the previous visit, but present at the next visit) as a function of HHA presence at the preceding year's visit and dependence level at that preceding year's visit. RESULTS: The dependence level at the previous year's visit was a significant predictor of HHA use at the next year's visit. Three specific items of the Dependence Scale (needing household chores done for oneself, needing to be watched or kept company when awake, and needing to be escorted when outside) were significant predictors of the presence of an HHA. CONCLUSION: The Dependence Scale is a valuable tool for predicting HHA use in AD patients. Obtaining a better understanding of home health care in AD patients may help delay NHP and have a positive impact on the health and well-being of both the caregiver and the patient.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Home Health Aides; Humans; Male; Middle Aged; Socioeconomic Factors